Intramedullary nailing as osteosynthesis technique for the fibula in total ankle arthroplasty via lateral approach - Carrasco, Alberto de Castro; Dorado, Patricia Domínguez; Martínez, Laura Anta; Alvarez-Val, Carmen (Journal of the Foot & Ankle, 2024)
Objective: To describe a variation in the final osteosynthesis technique for total ankle replacement (TAR) implantation through lateral approach. Methods: We retrospectively reviewed a series of cases dated between January 2022 and May 2023 in which intramedullary nailing was used as the osteosynthesis technique for the fibula during TAR implantation via lateral approach. Results: In all cases, skin scarring and soft tissue recovery to baseline were achieved in one and a half month to three months. Consolidation of the fibula occurred at an average of three months. No material was removed in any of the cases to date. Finally, patients were satisfied, resuming their previous activities. Conclusion: To our knowledge, this study is the first to investigate a modification of the osteosynthesis technique in the lateral approach to TAR. We believe the intramedullary nail for the fibula may be a useful tool to prevent soft tissue complications, requiring prospective and comparative studies to evaluate its efficacy. Level of Evidence IV; Therapeutic Studies; Case Series.